A Fractional Model of Bloch Equation in Nuclear Magnetic Resonance and its Analytic Approximate Solution - Sunil KUMAR (Walailak Journal of Science and Technology, 2013)
The purpose of this paper is to employ an analytical approach to the time fractional Bloch Nuclear Magnetic Resonance (NMR) flow equations. A comparative study of the numerical solutions and the well-known analytical solutions are discussed. Absolute error has been calculated to show the accuracy of the applied method. The numerical solutions show that only a few iterations are needed to obtain accurate approximate solutions. The fractional derivatives are described in the Caputo sense. Numerical results are presented graphically.